Modulation of virulence factors in biofilm-forming Klebsiella pneumoniae via selected South African medicinal plants and phytochemical compounds - Cosa, Sekelwa (University of Pretoria, 2023)
Thesis (PhD (Microbiology))--University of Pretoria, 2023.